Regulatory Governance and Chile's 1998-99 Electricity Shortage - Fischer, Ronald (World Bank, Washington, DC, 2014)
In the early 1980s Chile reformed its electricity sector, introducing a regulatory framework that became influential worldwide. But in 1998 and 1999 La Nina brought one of the worst droughts on record, causing a price system collapse, random power outages, and three-hour rotating electricity cuts. The authors study the interaction between regulatory incentives and governance during the 1998-99 electricity shortage, showing that the supply restriction could have been managed without outages. The shortage can be blamed on a rigid price system, which was unable to respond to large supply shocks, and on deficient regulatory governance, which led to a weak regulator unable to make the system work. The authors also show that the regulator's weakness stemmed not from lack of formal powers but from vulnerability to lobbyists and a lack of independence. Moreover, the regulator seems not to have fully understood the incentives in the price system during supply restrictions. The authors conclude that the Chilean shortage shows the limitations of a rigid price system requiring heavy regulatory intervention. This suggests that countries whose governance structures are ill suited to dealing with loopholes left by the law should rely as much as possible on market rules that clearly allocate property rights ex ante and leave the terms of contracts to be freely negotiated by private parties.